INFLUENCE OF CRITICAL SUCCESS FACTORS ON SUPPLY CHAIN PERFORMANCE OF COUNTY GOVERNMENTS IN KENYA - KIOKO, PATRICIA SYOMBUA; OCHIRI, Dr. GEORGE (International Journal of Supply Chain and Logistics, 2019)
Purpose: The purpose of the study was to examine influence of critical success factors on performance of county governments in Kenya with an aim of making recommendations on proper use. Methodology: The study employed a descriptive research design, targeting 163 procurement officers in the 5 of 13 county governments in Kenya which had a budget allocation of above Kshs 8 Billion according to FY 2017/2018 budgetary allocation by the National Treasury, the five were chosen because of their close proximity to Nairobi. The researcher preferred this method because it allows an in-depth study of the subject. Data was collected using self-administered questionnaires. Structured questionnaire was used to collect data. Data was analyzed using descriptive and inferential statistics. Quantitative data was analyzed using multiple regression analysis Results: The independent variables reported R value of .846 indicating that there is perfect relationship between dependent variable and independent variables. R square value of 0.716 which means that 71.6% of the corresponding variation in supply chain performance of the county governments can be explained or predicted by (quality index management, asset utilization management, schedule management and cost metrics management) which indicated that the model fitted the study data. The results of regression analysis revealed that there was a significant positive relationship between dependent variable and independent variable at (Î² = 1.240), p=0.00 <0.05). Conclusion: The study therefore establishes that; quality index management, asset utilization management, schedule management and cost metrics management influence supply chain performance of county governments. Policy recommendation: The study recommends that procurement officers should ensure that they strictly follow operational procedures to ensure that projects undertaken are of the right quality, in the right quantity, at the right time, to the right place from the right source. This will aim at satisfaction of customers in terms of cost, quality, and timeliness of the delivered product or service, minimizing administrative operating costs.